Clinical Implications of Circulating Tumor DNA Tumor Mutational Burden (ctDNA TMB) in Non‐Small Cell Lung Cancer. (13th March 2019) - Chae, Young Kwang; Davis, Andrew A.; Agte, Sarita; Pan, Alan; Simon, Nicholas I.; Iams, Wade T.; Cruz, Marcelo R.; Tamragouri, Keerthi; Rhee, Kyunghoon; Mohindra, Nisha; Villaflor, Victoria; Park, Wungki; et al.
Abstract: Background: Tissue tumor mutational burden (TMB) has emerged as a potential biomarker predicting response to anti‐programmed cell death‐1 protein receptor (PD‐1)/programmed cell death‐1 protein ligand (PD‐L1) therapy, but few studies have explored using circulating tumor DNA (ctDNA) TMB in non‐small cell lung cancer (NSCLC). Materials and Methods: A total of 136 patients with NSCLC with ctDNA testing were retrospectively evaluated from a single institution, along with a validation cohort from a second institution. ctDNA TMB was derived using the number of detected mutations over the DNA sequencing length. Results: Higher ctDNA TMB was significantly correlated with smoking history ( p < .05, chi‐squared test). Among patients treated with immune checkpoint inhibitors ( n = 20), higher ctDNA TMB was significantly correlated with shorter progressive free survival (PFS) and overall survival (OS; 45 vs. 355 days; hazard ratio [HR], 5.6; 95% confidence interval [CI], 1.3–24.6; p < .01, and OS 106 days vs. not reached; HR, 6.0; 95% CI, 1.3–27.1; p < .01, respectively). In a small independent validation cohort ( n = 12), there was a nonsignificant numerical difference for higher ctDNA TMB predicting shorter OS but not PFS. ctDNA TMB was not correlated with RECIST tumor burden estimation in the subset of patients treated with immune checkpoint blockade. Conclusion: The findings indicate that higher ctDNA TMB, at the current commercial sequencing length, reflects worse clinical outcomes. Abstract : Establishing noninvasive biomarkers for response to immune checkpoint blockade is important. This study explored the use of circulating tumor DNA tumor mutational burden (ctDNA TMB) in non‐small cell lung cancer (NSCLC). This article evaluates this novel biomarker and reports on the landscape and clinical utility of ctDNA TMB in NSCLC.